Re-designing a rapid response system: effect on staff experiences and perceptions of rapid response team calls - Richard Chalwin; Lynne Giles; Amy Salter; Karoline Kapitola; Jonathan Karnon (BMC, 2020)
Abstract Background Rapid Response Team (RRT) calls are clinical crises. Clinical and time pressures can hinder effective liaison between staff who call the RRT ('users') and those responding as part of the RRT ('members'). Non-technical skills (NTS) training has been shown to improve communication and cooperation but requires time and financial resources that may not be available in acute care hospitals. Rapid Response System (RRS) re-design, aiming to promote use of NTS, may provide an alternative approach to improving interactions within RRTs and between members and users. Methods Re-design of an existing mature RRS was undertaken in a tertiary, metropolitan hospital incorporating the addition of: 1) regular RRT meetings 2) RRT role badges and 3) a structured member-to-user patient care responsibility "hand-off" process. To compare experiences and perceptions of calls, users and members were surveyed pre and post re-design. Results Post re-design there were improvements in members' understanding of RRT roles (P = 0.03) and responsibilities (P < 0.01), and recollection of introducing themselves to users (P = 0.02). For users, after the re-design, there were improvements in identification of the RRT leader (P < 0.01), and in the development of clinical plans for patients remaining on the ward at the end of an RRT call (P < 0.01). However, post-re-design, fewer users agreed that the structured hand-off was useful or that they should be involved in the process. Both members and users reported fewer experiences of conflict at RRT calls post-re-design (both P < 0.01). Conclusion The RRS re-design yielded improvements in interactions between members in RRTs and between RRT members and users. However, some unintended consequences arose, particularly around user satisfaction with the structured hand-off. These findings suggest that refinement and improvement of the RRS is possible, but should be an ongoing iterative effort, ideally supported by staff training. Trial registration NCT01551160 . Registered: 12th March 2012.